Dietary Fibre Supplementation Improves Semen Production by Increasing Leydig Cells and Testosterone Synthesis in a Growing Boar Model - Lin, Yan; Wu, De; Che, Lianqiang; Fang, Zhengfeng; Xu, Shengyu; Feng, Bin; Zhuo, Yong; Li, Jian; Wu, Caimei; Zhang, Junjie; Li, Lujie (Frontiers in Veterinary Science, 2022)
Testicular development is imperative to spermatogenesis, and pre-puberty is the key period for testis development. Therefore, this study investigated the effects of fibre supplementation on testis development and its possible mechanism in a growing boar model. Thirty Yorkshire boars were randomly divided into a control group (Con) and a fibre group (Fibre) from d 0 to 90 after weaning, with three pigs per pen and five pens per treatment. Blood and testes were collected for analysis. Dietary fibre supplementation had no significant effect on average daily gain, average daily feed intake, or testicular volume. Boars fed with fibre had lower serum cholesterol (CHO) and low-density lipoprotein (LDL) levels compared to those fed with the Con diet; however, testicular CHO concentration in the Fibre was significantly higher than the Con group, and TG and LDL levels were significantly higher in the Fibre group (P < 0.01). Testicular histological analysis showed that seminiferous tubules and testicular germ cells of 120-day-old boars were densely arranged in the Fibre group, and the number of Leydig cells was significantly higher than that in the Con group (P < 0.001). Furthermore, the diet supplemented with fibre significantly decreased leptin, leptin receptor (Leptor), and luteinizing hormone (LH) concentrations in boar serum (P < 0.05), whereas follicle-stimulating hormone (FSH) and testosterone concentrations were significantly higher than those in the Con group (P < 0.05). Meanwhile, the expression of AMH, AMHR2, and SYCP3 genes related to proliferation and differentiation, and hormone-related genes STAR and SOCS3 were significantly upregulated (P < 0.05). OCCLUDIN expression was up-regulated, whereas CDH2 expression was down-regulated. In conclusion, increased fibre intake during the pre-puberty period is very important for Leydig cell proliferation, upregulating the expression of genes related to hormone synthesis, thereby promoting the secretion of testosterone and spermatogenesis.